Investigating Differentiated Learning Practices and their Influence on Multiple Domains of Early Childhood Development - Annisah Nurul Dzulaekha; Mohammad Syaifuddin; Mohamad Syahri (Sakura Digital Nusantara, 2026)
Purpose : This study examines the systematic use of differentiated learning in early childhood classrooms at Hang Tuah Kindergarten, Tarakan, with a focus on its observed associations across six developmental domains moral-religious, physical-motor, cognitive, linguistic, socio-emotional, and artistic. It addresses the research gap in holistic analyses that move beyond single-domain evaluations. Methods: A qualitative methodology was used, incorporating classroom observations, semi-structured interviews with educators, and analysis of children's work artifacts. Data triangulation included instructional techniques, instructor perspectives, and developmental markers. Evidence was categorized into observed behaviors, instructor reflections, and documented outputs, with quality ratings assigned for systematic comparison. Findings: The study highlighted consistent differentiation in content, process, and product, with content adaptation deemed